2018
DOI: 10.1186/s13287-018-0837-x
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic submucosal injection of adipose-derived mesenchymal stem cells ameliorates TNBS-induced colitis in rats and prevents stenosis

Abstract: BackgroundMesenchymal stem cells have potential applications in inflammatory bowel disease due to their immunomodulatory properties. Our aim was to evaluate the feasibility, safety and efficacy of endoscopic administration of adipose-derived mesenchymal stem cells (ASCs) in a colitis model in rats.MethodsColitis was induced in rats by rectal trinitrobenzenesulfonic acid (TNBS). After 24 h ASCs (107 cells) or saline vehicle were endoscopically injected into the distal colon. Rats were followed for 11 days. Dail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…It has been previously described that the reduction of systemic inflammation in this experimental model of colitis is mediated by the induction of regulatory CD25 + Foxp3 + CD4 + T cells in the colon and mLNs [ 33 , 46 ] together with a reduction in the levels of IL17 in the lamina propria mononuclear cells [ 45 ]. Furthermore, we have recently found that endoscopic administration of eASCs in the colon submucosa of TNBS-colitic rats attenuated the severity of colitis and reduced inflammation, which was associated to increased expression of Foxp3 and IL−10 mRNA in mLNs of eASC-treated rats [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously described that the reduction of systemic inflammation in this experimental model of colitis is mediated by the induction of regulatory CD25 + Foxp3 + CD4 + T cells in the colon and mLNs [ 33 , 46 ] together with a reduction in the levels of IL17 in the lamina propria mononuclear cells [ 45 ]. Furthermore, we have recently found that endoscopic administration of eASCs in the colon submucosa of TNBS-colitic rats attenuated the severity of colitis and reduced inflammation, which was associated to increased expression of Foxp3 and IL−10 mRNA in mLNs of eASC-treated rats [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…To clarify this, we performed a comprehensive survey for publications using MSCs in experimental animal models of inflammatory diseases (focusing mainly on sepsis, acute lung injury, acute respiratory distress syndrome, arthritis, and colitis). We identified the methodological details provided in each publication regarding origin and immunological matching of the MSCs used, the status of the cells prior to administration (trypsinized from culture or thawed after cryopreservation), and therapeutic outcome (Supporting Information Table S1; refs: ). Of the 92 publications reviewed, 40 used autologous/syngeneic (43%), 39 xenogeneic (42%), and 7 allogeneic (8%) MSCs (Table ).…”
Section: Mechanism Of Action; Current State Of the Artmentioning
confidence: 99%
“…In terms of the administration routes of MSCs, which might also contribute to the tremendously various outcomes of MSC treatment, our results illustrated that both the delivery of intravenous injections and submucosal injection by endoscopy could be conducive to the healing and recurrence of UC [18]. It is also reported that submucosal endoscopic injection using AD-MSCs could ameliorate TNBS-induced colitis, especially stenosis in rats [54]. Meanwhile, we have noticed from Nam and Cao’s studies that compared with using entire mouse BM-MSCs, application of extracellular vesicles (EVs) extracted from mouse BM-MSCs was more efficient in improving colon length [38, 48].…”
Section: Discussionmentioning
confidence: 83%